Análise da associação de células mononucleares de medula óssea a um arcabouço de osso bovino liofilizado - Kalaoun, Rosana (2014)
Mesenchymal stem cells hold great promise for tissues repair and regeneration, including bone defects. The association of these cells to a scaffold which resembles bone tissue structure and physiology is a major challenge in bone tissue engineering. The lyophilized bovine bone has a structure, chemical composition and mechanical properties similar to human bone marrow and acts as an excellent osteoconductive material. This in vitro study aimed to evaluate the growth of bone marrow mononuclear cells (BMMC) on a lyophilized bovine bone scaffold (Orthogen® - Baumer S.A., BR) covered with fibronectin; to verify if different cell densities interfere with the adhesion and proliferation of these cells and to evaluate whether the combination of platelet-rich plasma (PRP) interferes with adhesion and proliferation of BMMC grown on the lyophilized bovine bone scaffold. For this purpose, bone marrow cells obtained from a Kyoto rat were grown on blocks of lyophilized bovine bone coated with fibronectin in DMEM culture medium supplemented with 10% inactivated fetal bovine serum. The Orthogen® samples were distributed into four experimental groups, in triplicate, in three 24 wells culture plates and evaluated in three periods: 72 h, 96 h and 192 h. Group 1: lyophilized bovine bone + BMMC (5 x 104 cells / well); Group 2: lyophilized bovine bone + BMMC + PRP; Group 3: lyophilized bovine bone + fibroblasts (3T3); Group 4: lyophilized bovine bone + BMMC (15 x 104 cells / well). Cultures were incubated with the intercalating agent 4',6-diamidino-2-phenylindole (DAPI) for nuclear staining in order to evaluate the cell population density, by detection with confocal microscopy, of the number of cells adhered to the lyophilized bovine bone scaffolds, after 72 h, 96 h and 192 h. The analysis of the lyophilized bovine bone surface and the morphological aspects of the cells adhered to it was performed on one sample from each group, by scanning electron microscopy (SEM). Analysis of variance (ANOVA) with two factors showed a significant interaction between the main effects evaluated: group and time, with p < 0.001. Through the results of Bonferroni statistical test, significant difference was found in the average number of nuclei in the period of culture of 96 h in group 3, and the period of culture of 192 h in group 4, which was higher than the other groups. Through SEM analysis, mononuclear cells adhered to the lyophilized bovine bone scaffold were observed only in the groups 3 and 4, in the last, progressively, being already possible to observe cell morphology differentiation and to identify spherical and fusiform cells with cytoplasmic extensions. We concluded that BMMC cultured on a lyophilized bovine bone scaffold coated with fibronectin adhered and proliferated on the bone surface. BMMC cultured at a density of 15 x 104 cells / well, adhered and proliferated on the bone surface more evidently, when compared to the BMMC cultured at a density 5 x 104 cells / well, in the three culture periods evaluated. The association of PRP to BMMC culture on a lyophilized bovine bone scaffold increased, but not with statistical significance, the adhesion and proliferation on the bone surface.